2006
DOI: 10.1016/j.pharmthera.2005.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-target strategies for the improved treatment of depressive states: Conceptual foundations and neuronal substrates, drug discovery and therapeutic application

Abstract: Major depression is a debilitating and recurrent disorder with a substantial lifetime risk and a high social cost. Depressed patients generally display co-morbid symptoms, and depression frequently accompanies other serious disorders. Currently available drugs display limited efficacy and a pronounced delay to onset of action, and all provoke distressing side effects. Cloning of the human genome has fuelled expectations that symptomatic treatment may soon become more rapid and effective, and that depressive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
508
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 486 publications
(520 citation statements)
references
References 3,398 publications
7
508
0
5
Order By: Relevance
“…There is a possibility that those patients with depression having less dopaminergic activity in prefrontal cortex (due to highactive COMT enzyme) may respond better to ECT, which in turn increases dopaminergic activity. 2,10 However, studies of this topic are far from conclusive and further studies are needed to confirm these results. Our result is in line with Szegedi et al 11 who reported that COMT high (Val)-allele carriers responded better to treatment with mirtazapine in major depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a possibility that those patients with depression having less dopaminergic activity in prefrontal cortex (due to highactive COMT enzyme) may respond better to ECT, which in turn increases dopaminergic activity. 2,10 However, studies of this topic are far from conclusive and further studies are needed to confirm these results. Our result is in line with Szegedi et al 11 who reported that COMT high (Val)-allele carriers responded better to treatment with mirtazapine in major depression.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, the mechanism of the action of ECT is unknown. Several lines of evidence suggest that dopaminergic actions in the prefrontal cortex may be involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans and animals have shown a relationship between alterations in noradrenergic (NA) brain system function and behaviors associated with depression and anxiety (Ressler and Nemeroff, 2000;Millan, 2006). For example, the b 1 and b 2 adrenoceptors are known to participate in stress-related behavioral changes (Gorman and Dunn, 1993;Gurguis et al, 1999;Cecchi et al, 2002) and to mediate the effects of antidepressant treatment (Hancock and Marsh, 1985;Stahl et al, 1987;Manier et al, 1989;Holoubek et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, considerable efforts are invested in the search for better drugs (and other, nonpharmacotherapeutic approaches) for more effective treatment of depression. [2][3][4][5][6][7][8] There is a need for improved control not just of affective deficits, but also of other symptoms, such as insomnia, circadian desynchronization, sexual dysfunction, cognitive impairment, and pain. Moreover, depression shows high comorbidity with other serious CNS disorders (Table 1).…”
Section: From Highly Selective Agents To Multitarget Antidepressantsmentioning
confidence: 99%